Perceived benefits and barriers to yoga participation after stroke: A focus group approach. (February 2019) - Harris, A.; Austin, M.; Blake, T.M.; Bird, M.L.
Abstract: Background: and Purpose: There is increasing evidence to suggest yoga can be beneficial to health and wellbeing after stroke. The purpose of this study was to identify perceived benefits and barriers to yoga participation among adults with chronic stroke. Materials and methods: Twenty-six community dwelling adults (14 female, 12 male) who were at least 6-months post-stroke participated in four focus groups held at local stroke recovery meetings. Data was recorded and transcripts were analysed thematically. Results: Participants identified whole body benefits, the return of connection and feeling health in mind as the primary benefits of yoga. Perceived barriers included physical barriers to participation, cognitive challenges, environmental access, and financial limitations. Conclusion: Stroke survivors perceive yoga practice provides benefits in 'connectedness'. Future interventions should recognize the importance of yoga instructor training, focus on the mind-body connection aspects of yoga, and modifying activities to safely accommodate the physical abilities of the participants. Highlights: Yoga for people after stroke improves the mind-body connection regardless of physical ability. Yoga instructors require skills in adapting yoga for people of different abilities after stroke. There are both physical benefits and physical challenges of participating in yoga after stroke. Yoga practice is a tool to that people after stroke can use for stress management.